2021
DOI: 10.1007/s00214-021-02734-z
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking density functional theory methods for modelling cationic metal–argon complexes

Abstract: Noble gas chemistry is fascinating because noble gases can make formal chemical bonds with metal ions, despite their closed electronic configuration. Argon-metal ion complexes are particularly interesting since their bonding is halfway between dispersion and covalent interactions. Although many metal ion-noble gas complexes have been synthesized, there are still disagreeing theoretical descriptions about their bonding, which is not yet fully understood. Accurate experimental data is important as solid referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Dispersion forces were accounted for via the D3BJ dispersion-correction [ 35 ]. This level of theory was shown to be accurate and computationally efficient for describing the interactions in Au + -Ar m ( m ≤ 4) [ 21 ]. The geometries of the bare Au n + ( n = 3–20) clusters were adopted from previous works.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersion forces were accounted for via the D3BJ dispersion-correction [ 35 ]. This level of theory was shown to be accurate and computationally efficient for describing the interactions in Au + -Ar m ( m ≤ 4) [ 21 ]. The geometries of the bare Au n + ( n = 3–20) clusters were adopted from previous works.…”
Section: Methodsmentioning
confidence: 99%
“…One consequence of the relativistic effects in Au is an enhanced electron affinity [ 20 ], if compared, for instance, with Ag and Cu. The high electron affinity was shown to favor electron transfer from the Ng atom to Au in the AuNg + dimer and therefore the formation of a relatively strong bond [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This level of theory was selected based on two previous studies, where a correct description of Ng interactions with gold clusters was shown. 21,29 While for Au 2 Ng 4 + and + , a second stable configuration of the Ng atoms is shown in the Supporting Information. Importantly, this additional configuration also has three Ng atoms adsorbed on an atop coordination.…”
mentioning
confidence: 96%
“…This functional has also been used to calculate properties of Pd and Ag doped Au clusters, 25,31,32,44,45 and correctly predicted the vibrational modes of Au + ·Ar m and Pd + ·Ar m complexes. 46 An extensive isomer global search of PdAu n −1 + isomers was performed in ref. 31 .…”
Section: Methodsmentioning
confidence: 99%